External Validation of Major Adverse Cardiovascular Events’ Predictors in ST-Segment Elevation Myocardial Infarction Patients Undergoing Primary Percutaneous Coronary Intervention - Raharjo, Robert Adrianto; Herminingsih, Susi; Ardhianto, Pipin; Herry, Yan (RSUP Dr. Kariadi, 2021)
BACKGROUND: KARIADI risk score is a 0-to-9 point system based on Killip class, final TIMI flow, total ischemic time, creatinine level, blood glucose, systolic blood pressure, and age. This score was developed to predict the risk of in-hospital major adverse cardiovascular events (MACE) (a composite of death, stroke, urgent revascularization, cardiogenic shock, acute pulmonary edema, or arrhythmia) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous intervention (PPCI), but its performance has never been validated externally. OBJECTIVE: To perform external validation on KARIADI risk score. METHOD: This study was a prospective cohort study on 109 STEMI patients undergoing PPCI in Dr. Kariadi General Hospital during January-November 2020. Each sample underwent KARIADI risk score assessment and follow-up for in-hospital MACE. The risk score validation was performed by assessing calibration [measured with calibration-in-the-large (alpha), calibration slope (beta), and calibration plot] and discrimination performance [measured with c-statistic and receiver operating characteristic curve). RESULT: Eighteen patients (16.5%) had MACE. KARIADI risk score demonstrated unsuitable calibration (alpha -0.39, beta 0.71, unfit calibration plot) and moderate discrimination performance (c-statistic 0.75, 95% CI 0.62-0.87). CONCLUSION: KARIADI risk score is not valid in predicting in-hospital MACE in patients with STEMI undergoing PPCI. Keywords: ST-segment elevation myocardial infarction, primary percutaneous coronary intervention, KARIADI risk score, external validation